2022
DOI: 10.1099/mgen.0.000765
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and phenotypic analyses of diverse non-clinical Acinetobacter baumannii strains reveals strain-specific virulence and resistance capacity

Abstract: Acinetobacter baumannii is a critically important pathogen known for its widespread antibiotic resistance and ability to persist in hospital-associated environments. Whilst the majority of A. baumannii infections are hospital-acquired, infections from outside the hospital have been reported with high mortality. Despite this, little is known about the natural environmental reservoir(s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 100 publications
(191 reference statements)
2
34
0
Order By: Relevance
“…We previously reported that the environmental A. baumannii strain E-072658 carries eight plasmids [29]. As also previously reported, E-072658 belongs to a novel sequence type (ST649) and it is not related to any other strains characterized to date (including all clinical and environmental strains).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…We previously reported that the environmental A. baumannii strain E-072658 carries eight plasmids [29]. As also previously reported, E-072658 belongs to a novel sequence type (ST649) and it is not related to any other strains characterized to date (including all clinical and environmental strains).…”
Section: Resultsmentioning
confidence: 88%
“…baumannii strain E-072658 [28], recovered in recycled fibre pulp in a Finnish paper mill, and Hamidian et al . [29] were analysed in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations